Writing Onê: Deviant Orthography and Heternormativity in Contemporary Japanese Lifestyle Culture. Issue 1 (May 2013) - Maree, Claire
Since the turn of the millennium, Japanese variety television has witnessed a revival in onê-kyara (queen personalities). In contemporary lifestyle media, the trans-gendered onê -personality figure is demonstrative of how suitable consumption and personal effort can bring forth the transformational happiness of the individual. The transgressive, radical potential of the figure of transformative non-normative gender is muffled by the onê -personality's positioning within variety television as a friendly expert of extraordinary and often comical proportions. Language is one of the key sites where the tensions of critical expertise and queerness are negotiated via synthetic friendship and comic relief. In lifestyle media, onê-kyara-kotoba (queen-personality-talk) is juxtaposed with conventional Japanese and emerging practices of digital orthography. This social practice of writing effectively facilitates the contemporary fetish of the onê (queen), and the consumption of homosexual and trans-gendered lifestyle experts selling the promise of heteronormative romantic love.